Coalescence of Magnetic Flux Ropes Within Interplanetary Coronal Mass Ejections: Multi-cases Studies - Zhao, Yan; Feng, Hengqiang; Liu, Qiang; Zhao, Guoqing (Frontiers in Physics, 2019)
Coronal mass ejections (CMEs) are intense solar explosive eruptions and have significant impact on geomagnetic activities. It is important to understand how CMEs evolve as they propagate in the solar-terrestrial space. In this paper, we studied the coalescence of magnetic flux ropes embedded in five interplanetary coronal mass ejections (ICMEs) observed by both ACE and Wind spacecraft. The analyses show that coalescence of magnetic flux ropes could persist for hours and operate in scale of hundreds of earth radii. The two merging flux ropes could be very different in the axial orientation and the plasma density and temperature, which should complicate the progress of coalescence and have impact on the merged structures. The study indicates that coalescence of magnetic flux ropes should be an important factor in changing the magnetic topology of ICMEs.